2017
DOI: 10.1002/jmor.20775
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of endocrine pancreatic granules during pancreatic differentiation in the grass snake, Natrix natrix L. (Lepidosauria, Serpentes)

Abstract: We used transmission electron microscopy to study the pancreatic main endocrine cell types in the embryos of the grass snake Natrix natrix L. with focus on the morphology of their secretory granules. The embryonic endocrine part of the pancreas in the grass snake contains four main types of cells (A, B, D, and PP), which is similar to other vertebrates. The B granules contained a moderately electron-dense crystalline-like core that was polygonal in shape and an electron-dense outer zone. The A granules had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 122 publications
(172 reference statements)
0
3
0
Order By: Relevance
“…It was also described in the pancreatic duct cells of adult vertebrates (Kobayashi, ). It can be supposed that the appearance of glycogen at stage VI in the embryonic pancreatic duct cells of the grass snake is correlated with the beginning of insulin synthesis by the B cells (Kowalska & Rupik, ). Some authors suggested that insulin may participate in the synthesis of glycogen in ovo (Benzo & Green, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also described in the pancreatic duct cells of adult vertebrates (Kobayashi, ). It can be supposed that the appearance of glycogen at stage VI in the embryonic pancreatic duct cells of the grass snake is correlated with the beginning of insulin synthesis by the B cells (Kowalska & Rupik, ). Some authors suggested that insulin may participate in the synthesis of glycogen in ovo (Benzo & Green, ).…”
Section: Discussionmentioning
confidence: 99%
“…After rinsing in phosphate buffer, the material was dehydrated first in a graded alcohol series and then in acetone and embedded in an Epoxy Embedding Medium Kit (Sigma, St. Louis, MO). This procedure of fixation appears to be the best for different embryonic reptilian tissues (Kowalska & Rupik, ; Rupik, ; Rupik, Kowalska, Swadźba, & Maślak, ; Swadźba & Rupik, ). The Epon blocks were cut on a Leica Ultracut UCT ultramicrotome (Leica, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…They were half-buried in a 1:1 mixture of sand and peat and kept in plastic storage boxes for food with transparent walls. Embryonic development of Natrix embryos in the laboratory conditions lasted 30–33 days [ 59 , 60 ]. During the developmental period, from egg laying to hatching, embryos were isolated at the same intervals of time.…”
Section: Methodsmentioning
confidence: 99%